Penile Ectopic Testis (PET) Case Report in Adulthood in Rural Area of Africa: An Uncommon Cause of Dyspareunia - Efoe-Ga, Amouzou; Ananivi, Sogan; Komi, Sikpa; Damigou, Sambiani; Ekoue, Dosseh (European Scientific Journal, ESJ, 2018)
Penile ectopic testis is a rare congenital abnormality with an etiopathogenesis poorly understood nowadays. We report a case of a 19 years old boy admitted for left groin hernia with dyspareunia whose management in rural area consisted in an orchidopexy in dartos completed by a normal sperm count and a normal testicular biopsy.